2018
DOI: 10.1016/j.jseaes.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Using chemical compositions of sediments to constrain methane seepage dynamics: A case study from Haima cold seeps of the South China Sea

Abstract: Cold seeps frequently occur at the seafloor along continental margins. The dominant biogeochemical processes at cold seeps are the combined anaerobic oxidation of methane and sulfate reduction, which can significantly impact the global carbon and sulfur cycles. The circulation of methane-rich fluids at margins is highly variable in time and space, and assessing past seepage activity requires the use of specific geochemical markers. In this study, we report multiple sedimentary proxy records for three piston gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…Since the 1990's, high-resolution seismic surveys have been carried out to delineate the distribution of bottom-simulating reflectors (BSR) and determine the prospecting area of gas hydrates. Through several hydrate survey expeditions, six promising hydrate-bearing areas including Dongsha, SW Taiwan, Xisha, Qiongdongnan, Shenhu, and Beikang have been confirmed to date [13][14][15][16][17][18][19][20]. Besides, more than 40 cold seepage sites have been indicated by the occurrence of 13 C-depleted authigenic carbonate and seep-associated fauna and anomalous pore water and sediment geochemistry influenced by fluid seepage [6,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990's, high-resolution seismic surveys have been carried out to delineate the distribution of bottom-simulating reflectors (BSR) and determine the prospecting area of gas hydrates. Through several hydrate survey expeditions, six promising hydrate-bearing areas including Dongsha, SW Taiwan, Xisha, Qiongdongnan, Shenhu, and Beikang have been confirmed to date [13][14][15][16][17][18][19][20]. Besides, more than 40 cold seepage sites have been indicated by the occurrence of 13 C-depleted authigenic carbonate and seep-associated fauna and anomalous pore water and sediment geochemistry influenced by fluid seepage [6,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The difference of estimated duration of constant methane flux between these two approaches may suggest that the barite front was not a result of the recent increase in methane flux inducing the kink-type sulfate profile. Instead, it is more likely that the SMTZ has experienced several fluctuations in depth, considering the episodic pulses of upward methane flux which have occurred in this area as shown by previous studies [25,32,33]. However, this decoupled record between sediments and porewaters is commonly observed at cold seeps [74][75][76][77] and is considered to reflect the variations of methane fluxes and the resulting SMTZ in the sedimentary column [74].…”
Section: Formation Mechanisms Of the Nonlinear Porewatermentioning
confidence: 89%
“…Previous studies have suggested that microbial methane was the main hydrocarbon source with minor contributions of oil-derived compounds and pyrolysis gas at the Haima cold seeps [32,33,89,90]. Gas chimney structures, which are well developed around the Haima cold seeps, might serve as conduits for the upward migration of biogenic gas from the underlying free gas reservoir beneath the GHSZ to shallow sediments [29,42].…”
Section: Geofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…As and Sb are occasionally reported for sediments that underwent the influence of hydrothermal-fluid circulation or exhalation (plumes; Zeng et al, 2018 and references therein); however, associations of these two elements have been seldom mentioned for sediments impacted by cold (hydrocarbon) seepage (Tribovillard et al, 2013;Hu et al, 2014;Chen et al, 2016;Wang et al, 2018Wang et al, , 2019aWang et al, , 2019bZwicker et al, 2018). Regarding cold seeps, most often, analyses are performed on associated authigenic minerals such as carbonates and/or sulfides, but only rarely on bulk sediments as is the case in the present study.…”
Section: Enrichments Inmentioning
confidence: 99%